1997
DOI: 10.1097/00006534-199703000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Sequelae after Pedicled TRAM Flap Breast Reconstruction

Abstract: A considerable interest in autologous tissue breast reconstructions has developed recently, especially since Food and Drug Administration (FDA) experts have raised the polemic on silicone implants. Although such enthusiasm for the transverse rectus abdominis musculocutaneous (TRAM) flap is justified in what concerns the final cosmetic result of the reconstructed breast, the risk of abdominal sequelae should be explained to the patient. Abdominal scarring, parietal weakness, strength loss, and back pain have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 3 publications
2
17
0
3
Order By: Relevance
“…[15][16][17][18][19][20] However, some difficulties may occur in daily living, sports, or professional activities, likely because of the rectus abdominis strength deficit. Kind et al 21 and Edsander-Nord et al 22 have demonstrated that the harvest of a TRAM flap while preserving one-third to two-thirds of the muscle does not significantly preserve abdominal strength.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] However, some difficulties may occur in daily living, sports, or professional activities, likely because of the rectus abdominis strength deficit. Kind et al 21 and Edsander-Nord et al 22 have demonstrated that the harvest of a TRAM flap while preserving one-third to two-thirds of the muscle does not significantly preserve abdominal strength.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of both rectus abdominis muscles, which is required for a conventional bipedicled TRAM flap or conventional unipedicled TRAM/ conventional unipedicled TRAM flap, produces measurably greater abdominal weakness 22,23 and reduction in the ability to perform sit-ups 6,24 than does loss of only one rectus abdominis muscle, which is required for a conventional unipedicled TRAM flap. Concern over loss of abdominal function has led some authors to recommend abandoning the bipedicled technique, 7,25 but this view is not universally accepted.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why some surgeons have moved from pedicled TRAM flaps to free perforator flaps is to try to reduce the morbidity of the donor site and preserve abdominal wall integrity and function [28][29][30] . The complications encountered with techniques using lower abdominal tissue for breast reconstruction are related to repair techniques of the abdominal wall and the flap vascularization.…”
Section: Breast Reconstruction With Lower Abdominal Tissuementioning
confidence: 99%